A Software Reliability Model Using Quantile Function - Bijamma Thomas; Midhu Narayanan Nellikkattu; Sankaran Godan Paduthol (Journal of Probability and Statistics)
We study a class of software reliability models using quantile function. Various distributional properties of the class of distributions are studied. We also discuss the reliability characteristics of the class of distributions. Inference procedures on parameters of the model based on L-moments are studied. We apply the proposed model to a real data set.